Computational aspects of model acquisition and join geometry for the virtual reconstruction of the atrahasis cuneiform tablet - Collins, Tim; Woolley, Sandra; Gehlken, Erlend; Ch'ng, Eugene (2018)
The epic of Atrahasis is one of the most famous pieces of ancient Mesopotamian literature. The account has survived millennia on sets of clay tablets inscribed with cuneiform script; a sophisticated early writing system comprising signs formed from wedge-shaped impressions. The third tablet belonging to one of the most complete copies of the Atrahasis epic is broken. For over fifty years, one fragment, held in Geneva, was believed to join with another held in London. However, due to their 1000 km separation, the join had never been physically tested. This paper contributes a technological account of the successful virtual joining of the fragments [1]; the first ever longdistance virtual join of its type.